UPAYA FOOD AND BEVERAGE PRODUCT DALAM MEMPERTAHANKAN STANDAR MAKANAN DI LABERSA TOBA HOTEL AND CONVENTION CENTRE BALIGE - Asnaria Siadari; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This study aims to analyze the efforts made by Labersa Toba Hotel Balige in maintaining high food standards through aspects such as food quality, hygiene and sanitation, food storage, food processing, food presentation, menu variety, and service. This study uses a qualitative descriptive method with data collection techniques through interviews, observation, and documentation studies. Respondents in this study were food and beverage product staff. Food product quality standards are also important to ensure food products are safe for consumption and meet nutritional requirements. Strategies that can be implemented to improve the quality of food products include maintaining the quality of raw materials, establishing good production procedures, paying attention to cleanliness and sanitation, training human resources, and conducting regular quality tests. The results of the study show that Labersa Toba Hotel Balige has high food standards and fulfills various aspects regulated by the hospitality industry. The efforts made by Labersa Toba Hotel Balige to maintain high food standards include selecting high quality food ingredients, implementing strict sanitation and hygiene procedures, using modern technology for storing food ingredients, good food processing, attractive food presentation, and friendly and effective service. Keywords : Effort, Food Standard, Quality